The “Superilles” strategy in Barcelona, Spain: people-centered planning - Pasquotto, Geise Brizotti [UNESP]; Salcedo, Rosio Fernandéz Baca [UNESP] (University Nove de Julho, 2024)
Objective of the Study: Present and investigate the impacts of an innovative strategy called superilla, implemented in Barcelona city (Spain). Methodology: The research is divided into two stages: i) Theoretical exploration of the superilla concept and its sustainable principles (pedestrian priority, reduction in vehicle traffic, urban mobility, creation of open spaces and green areas, urban furniture, reduction of air pollution, among others) and ii) Impacts analysis of the superilla implemented in Barcelona, through case studies: PobleNou and Sant Antoní. Originality/Relevance: Although the superilles strategy in Barcelona represents a milestone for sustainability, there is a scarcity of discussions on the subject in the Brazilian context. Main Results: The study outlined the implementation phases of the superilles and highlighted six key points of the intervention, such as: i) modal hierarchy; ii) regional issue, iii) coordination between projects; iv) popular participation, v) exportable model and vi) renaturalization of the city. Contributions: This research focuses on investigating the processes occurring in the urban intervention of superilles, making their understanding more in-depth and disseminating this process in Brazil, in order to contribute to the new urban strategies dissemination.
La estrategia Superilles en Barcelona, España: planificación centrada en las personas
A estratégia das “Superilles” em Barcelona, Espanha: planejamento centrado nas pessoas
Keywords: Barcelona; mobility; open spaces; public policies; superblock